A new high‐pressure polymorph of phosphoric acid. Issue 6 (16th November 2017) - Bull, Craig L.; Funnell, Nicholas P.; Pulham, Colin R.; Marshall, William G.; Allan, David R.
Abstract : The high‐pressure behaviour of monoclinic phosphoric acid is presented and a new high‐pressure orthorhombic phase is reported. The molecule–molecule interaction energies of the orthorhombic phase are shown to be more attractive than those of the low‐pressure monoclinic phase. Abstract : The high‐pressure structural behaviour of phosphoric acid is described. A compression study of the monoclinic phase, using neutron powder diffraction and X‐ray single‐crystal diffraction, shows that it converts to a previously unobserved orthorhombic phase on decompression. Compression of this new phase is reported up to 6.3 GPa. The orthorhombic phase is found to be more efficiently packed, with reduced void space, resulting in a larger bulk modulus. Molecule–molecule interaction energies reveal a more extensive network of increased attractive forces in the orthorhombic form relative to the monoclinic form, suggesting greater thermodynamic stability.